2005
DOI: 10.1111/j.1461-0248.2005.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

New techniques and findings in the study of a candidate allelochemical implicated in invasion success

Abstract: Allelopathy has been hypothesized to promote the success of invasive plants. Support for the role of allelopathy in invasions has emerged from research on the candidate allelochemical ())-catechin, which is secreted by spotted knapweed. Here we describe new methods to quantify catechin in liquid and soil. With a new technique, we assayed catechin production by individual plants in liquid media and found levels up to two orders of magnitude less than previously reported. An acetone/water solution provided consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
137
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 26 publications
(88 reference statements)
4
137
4
1
Order By: Relevance
“…These variable data are likely due to the efficiency of the extraction method and soil type. The extraction yield of catechin was 100% with methanol (Bais et al 2002;Thelen et al 2005) but was also lower from 0 to 17% depending on the soil types (Blair et al 2005). Blair et al (2005) showed that 75:25% acetone/water solution containing 0.1% H 3 PO 4 was the most efficient extractant among nine different solutions tested to extract catechin from soil.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These variable data are likely due to the efficiency of the extraction method and soil type. The extraction yield of catechin was 100% with methanol (Bais et al 2002;Thelen et al 2005) but was also lower from 0 to 17% depending on the soil types (Blair et al 2005). Blair et al (2005) showed that 75:25% acetone/water solution containing 0.1% H 3 PO 4 was the most efficient extractant among nine different solutions tested to extract catechin from soil.…”
Section: Introductionmentioning
confidence: 97%
“…However, experimental conditions can markedly affect the concentration of the bio-available fraction of flavonoids. This has been found to range from 0 to 2.4 (Blair et al 2005), 5 to 35 (Weir et al 2003), 0 to 113 (Ridenour et al 2008), and 83 to 185 μg ml −1 (Bais et al 2002). These variable data are likely due to the efficiency of the extraction method and soil type.…”
Section: Introductionmentioning
confidence: 99%
“…Thorpe et al (2009) discovered from field experiments on two continents that some species in the introduced range of the controversial forb Centaurea maculosa Lam. (Callaway and Ridenour 2004;Bais et al 2003;Blair et al 2005;Duke et al 2009a, b) had reduced growth compared with co-occurring species in its native range which did not. This implied a level of adaptation in plant communities to phytotoxic compounds in the alleged allelopathic species through shared evolutionary history, which was absent in the introduced range.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence exists refuting the role of (-)-catechin, the phytotoxin principally used in building a case for the NWH as an allelochemical promoting invasiveness of spotted knapweed (Centaurea maculosa Lam.). Blair et al (2005) found no measurable catechin in soils of spotted knapweed sites using new methods to quantify catechin. Duke et al (2009a, b) refuted the mode of action of catechin causing damage by oxidation, claiming it to be a strong antioxidant that is rapidly denatured by extracellular root enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies include those on: juglone effects on root plasma membrane H + ATPase activity and root water uptake (Hejl and Koster 2004); the use of polydimethylsiloxane materials to quantify levels of the photosynthesis inhibitor sorgoleone in the rhizosphere of sorghum plants (Weidenhamer 2005); the critical evaluation of the contribution of (±)-catechin to invasion success of spotted knapweed (Blair et al 2005(Blair et al , 2006; degradation of soluble phenolics by ectomycorrhizal fungi, thus controlling species interactions in black spruce stands (Zeng and Mallik 2006); selective phytotoxicity of L-DOPA because of differential polyphenol oxidase activity in barnyard grass and lettuce, thus mediating reactive oxygen species and/or free radical species (Hachinohe and Matsumoto 2007); and differential gene expression in rice under low nitrogen due to stronger activation of genes that function in synthesis of allelochemicals (Song et al 2008).the term allelopathy. In his experiments, he used the odor of apple peels, mainly comprised of ethylene, as a model system to explore effects of volatile emissions on the development of a range of plant species.…”
Section: Introductionmentioning
confidence: 99%